A novel serous ovarian carcinoma model induced by DMBA: Results from OncoTherad® (MRB-CFI-1) immunotherapy preclinical testing - Ribeiro de Souza, Bianca; Oliveira, Gabriela; Leme, Giovana; Brum Reis, Ianny [UNESP]; Augusto Tossini Cabral, Felippe; Lima Baggio de Paula, Juliane; Henrique da Silva Santos, Daniel; Ronca Felizzola, Claudia; Durán, Nelson; Anglesio, Michael; José Fávaro, Wagner (Elsevier, 2025)
Aims: The term ovarian carcinoma (OC) refers to a heterogeneous collection of five distinct diseases known as histotypes. While histotype-specific treatment is still a clinical challenge in OC, well-characterized models are required for testing new therapeutic strategies. We employed OncoTherad® (MRB-CFI-1), an interferon (IFN-γ)-stimulating nano-immunotherapy mediated by Toll-like receptors (TLR) 2/4, in association or not with Erythropoietin (EPO) in a chemically-induced ovarian cancer model. Besides characterization of the therapies effects, we also assessed whether the animal model was representative of human OC by providing histotype classification. Main methods: Thirty-five Fischer rats were distributed into five groups: Control (Sham surgery); Cancer (7,12-dimethylbenzoanthracene – DMBA injection in the ovarian bursa, 1.25 mg/kg); OncoTherad® (20 mg/kg intraperitoneal); EPO (8.4 µg/kg intraperitoneal); and OncoTherad+EPO (same doses). Ovaries were formalin-fixed into paraffin-embedded blocks. TLR pathway and the inflammatory response profile were evaluated by immunohistochemistry (IHC). After DNA extraction and tissue microarray construction, we assessed typical gene mutations directly (Sanger sequencing) or indirectly (IHC surrogates) and examined biomarkers of different OC histotypes. Key findings: OC induction decreased TLR2, TLR4, and proinflammatory cytokines. OncoTherad® alone or associated with EPO modulated the OC microenvironment to a cytotoxic immune profile through stimulation of the TLR4-mediated non-canonical pathway. EPO stimulated TLR2-mediated canonical pathway and notably increased Tregs. Significance: The features analyzed favored interpretation of our DMBA-induced tumor model as predominantly low-grade, serous carcinoma-like, in which treatments with OncoTherad® and EPO showed immunomodulatory properties related to the reduction of ovarian lesions.
Keywords: Erythropoietin; IHC biomarkers; Nano-immunotherapy; OncoTherad; Ovarian cancer; Toll-like receptors